2009
DOI: 10.1107/s0108768109044899
|View full text |Cite
|
Sign up to set email alerts
|

[Ru(py)4Cl(NO)](PF6)2·0.5H2O: a model system for structural determination and ab initio calculations of photo-induced linkage NO isomers. Erratum

Abstract: In the paper by Cormary et al. [Acta Cryst. (2009), B65, 612–623] two authors were inadvertently omitted from the author list and one name was given incorrectly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 0 publications
1
20
0
Order By: Relevance
“…The photochromismo fr utheniumn itrosyl complexes and its capability to photorelease nitric oxide has numerous applications, from material engineering to digitali nformation storage up to the field of photodynamict herapy. [1][2][3] In this category, trans-[RuCl(NO)(py) 4 ] 2 + (Scheme 1) has attracted considerable attentiond ue to its reversible high photoswitching ability by using different laser wavelengths: [4][5][6] On continuous light irradiation at approximately4 73 nm for 1h,ac onversion yield of approximately 100 %i sa chieved on as ingle crystal, while subsequent irradiation at 980 nm regenerates the originalc rystal. [5] In contrast, NO dissociation only occurs with low quantum yield in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…The photochromismo fr utheniumn itrosyl complexes and its capability to photorelease nitric oxide has numerous applications, from material engineering to digitali nformation storage up to the field of photodynamict herapy. [1][2][3] In this category, trans-[RuCl(NO)(py) 4 ] 2 + (Scheme 1) has attracted considerable attentiond ue to its reversible high photoswitching ability by using different laser wavelengths: [4][5][6] On continuous light irradiation at approximately4 73 nm for 1h,ac onversion yield of approximately 100 %i sa chieved on as ingle crystal, while subsequent irradiation at 980 nm regenerates the originalc rystal. [5] In contrast, NO dissociation only occurs with low quantum yield in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…As reported in ref.,1e if other factors are equal, the degree of population of the metastable Ru–O–N state (MS1) produced from the Ru–N–O ground state (GS) after light irradiation decreases in the sequence of trans ligands H 2 O > Cl > Br after the replacement of the pyridine (Py) ligands at the cis positions to the nitrosyl group by a polydentate aromatic conjugated system [bipyridine (bpy), terpyridine]. The largest populations of the metastable states of NO have been achieved for the complex [Ru(NO)(Py) 4 Cl][PF 6 ] 2 3 with more than 90 % after irradiation and for [RuCl(NO) 2 (PPh 3 ) 2 ]BF 4 with ca. 70 % 2.…”
Section: Introductionmentioning
confidence: 99%
“…[5d, f, g] High conversion levels have also been achieved in nitrosyl linkage isomer systems; in 2009 Cormary et al reported 92 % excitation to the h 1 -ON isomer (MS1) in the complex [RuCl(NO)py 4 ](PF 6 )· 1 = 2 H 2 O (py = pyridine). [9] Schaniel and Woike have shown that high levels of conversion are only possible when there is sufficient energy difference between the two forms to avoid an equilibrium becoming established. [10] A high level of excitation, one that is both controllable and reproducible, is highly desirable if such systems are to have any real application, for example, in data storage or opto-electronic devices.…”
Section: Introductionmentioning
confidence: 99%